MATHCAD based printed microwave LPF simulation package - Esa, Mazlina; Hashim, Noor Azlina; Kanthan, Gunabalan (2000)
A simulation package for a printed microwave low pass filter (LPF) based on tbe powerful mathematical solver MatbCAD Premium 2000 bas been developed. The chosen structure of the LPF is the stepped-impedance type. Tbe developed package is mainly intended for student usage in tbe Microwave Laboratory of Universiti TekDologi Malaysia. However, assignments for the Microwave subject can also be given to undergraduate students. Challenging assignments may be given to tbe Masters students for. tbeir MicrowavelRF subject. Tbe development of sucb educational design and simulation package belps tbe university in saving large amount of costs for buying laboratory experimental set-ups.